Total cavopulmonary and atriopulmonary connections are associated with reduced heart rate variability. Issue 6 (1st December 1999) - Butera, G; Bonnet, D; Iserin, L; Sidi, D; Kachaner, J; Villain, E
Abstract : AIM: To determine whether cavopulmonary connections are associated with abnormalities of heart rate variability. METHODS: Heart rate variability was studied by 24 hour Holter monitoring in 39 patients (mean (SD) age 12.2 (4.1) years) who underwent cavopulmonary connection operations (partial in 12, total in 13, and atriopulmonary in 14). Two control groups were used: 18 healthy children (11.1 (2.5) years) and 16 patients (11.7 (4.3) years) undergoing cardiovascular surgery for biventricular repair of congenital heart disease. All patients were in sinus rhythm and had normal left ventricular function. Four time domain indices were calculated: mean duration of RR intervals (RR), standard deviation of all RR intervals (SD), square root of the mean squared differences of successive RR intervals (r-MSSD), and percentage differences of successive RR intervals of > 50 ms duration (pNN50). Four frequency domain indices were calculated: total power (TP), low frequency (LF), high frequency (HF), and the LF:HF ratio. RESULTS: Heart rate variability indices were identical in the two control groups. Significantly reduced heart rate variability was found in patients with total cavopulmonary connections and atriopulmonary connections compared with the two control groups. In patients with partial cavopulmonary connections, heart rate variability was reduced compared with healthy controls. No differences in heart rate variability could be related to clinical status (New York Heart Association functional class), number of surgical interventions, or presence of right atrial enlargement. CONCLUSIONS: Patients with cavopulmonary connections have significantly reduced heart rate variability and a particularly low vagal drive.